Hippotherapy as an accompaniment to therapy in children with autism - Magdalena Czelej; Konrad Gładysz; Justyna Szydłowska; Olga Żuchnik; Olgierd Król; Piotr Kwiatkowski; Beata Kuczyńska; Aleksander Kłos; Krzysztof Gieroba; Marcin Szydłowski (Kazimierz Wielki University, 2022)
Introduction: Autism is defined as difficulties in relating and communicating with other people and repetitive, specific behaviors. It is a developmental disorder, manifested before the age of 3. Increasingly, parents' awareness is resulting in reaching for a variety of therapies to help children on the spectrum develop properly. The interdisciplinary method that is hippotherapy stimulates physical and mental contact with the horse. Therefore, it can be assumed that this is a method that significantly helps the development and such children. Aim of the study: Compile publicly available studies and publications and determine whether hippotherapy has a beneficial effect on the development of children with autism. Materials and methods: A review of publications and studies available on Google Scholar and PubMed was made, using the phrases "autism" ; autism hippotherapy" ; "development of children with autism " ; "hippotherapy". Results: The higher standard of living nowadays and the deeper interest in the methods available for the therapy of children with ASD, allows parents to reach for non-standard solutions such as hippotherapy. Demonstrating the positive impact of activities with horses is the subject of many scientific studies. Studies conducted allow us to believe that, it has a beneficial effect on the development of people on the spectrum, through stimulation in the emotional, physical and social areas. Based on a review of the literature for the purpose of this article, it can be concluded that hippotherapy has a positive effect as an accompaniment to therapy for children with autism. Conclusion: Pharmacological treatment is the easiest way to deal with the symptoms of autism, but does not eliminate social deficits and emotional disorders. A number of therapies have emerged to help children on the spectrum develop: art therapy, Biofeedback, Brain Gymnastics, Logorytime . Incorporating hippotherapy into the child's treatment process allows the therapy to be complementary on many levels. Many studies have emerged confirming the positive impact on the development of a child on the spectrum, but there is no golden mean to cure this type of disorder.